Между Россией, Литвой и Польшей: судьба художника вильнюсской школы ХХ века (жизнь и творчество Стефана Нарембского) - Червонная С. М. (ИД «Среда», 2020)
It cannot be said that the creative biography of the artist-architect Stefan Narębski (1892–1966) remains a completely unknown page in the history of art, but everything that has been written and published so far about the life and work of Stefan Narębski is only the top of the iceberg which is his complete biography. The author restores many forgotten and unknown facts of this biography, mainly based on the materials of the Archive of the Nicolaus Copernicus University, first of all, the artist’s own notes (“Diaries”), which had never been published before. Discoveries of this kind relate primarily to the childhood and adolescence of Narębski, held in the Caucasus and Vilnius; his participation in the 1905 revolution; his educational and creative activities in Włocławek in the 1920s; his connections with Stephen Batory University; as well as the repressions that he faced both during the years of the Nazi occupation of Lithuania and during the restoration of Soviet power here, in 1944–45. In the artistic heritage of Narębski, a close-up is highlighted by the types of residential buildings developed by him, educational institutions (museum, school, university department), modern churches, projects for the artistic transformation and decoration of public interiors (the residence of the archbishop; town halls in Vilnius and Torun). The theoretical development of the artistic training program for masters of architectural design (design and decoration of interiors), carried out by Narębski, and the practical implementation of this program at the Nicolaus Copernicus University contained an innovative beginning and provided the most important breakthrough of Polish post-war artistic pedagogy towards a modern, progressive methodology. Of great importance is the international aspect of the work of Narębski, whose personal biography is connected not only with Poland and the strongest impulses of Polish patriotism, but also with Lithuania, Russia, Belarus, Ukraine (with the places where he studied, lived, worked, built and planned the construction of new objects). His contribution to the development of art and artistic pedagogy is subject to measurement on the scale of not only national but also Eastern European culture.
Keywords: Belarus; Belarus; biography; biography; Poland; Poland; Russia; Russia; Stefan Narębski; Stefan Narębski; history of art; history of art; artistic heritage; artistic heritage; decoration; decoration; Eastern European culture; Eastern European culture; Lithuania; Lithuania; Ukraine; Ukraine